2006
DOI: 10.1292/jvms.68.1207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ovary Lipid of Skipjack Tuna (Katsuwonus pelamis) on Anxious Behavior in Rats

Abstract: ABSTRACT. Ovary lipid of Skipjack tuna (OLS) (Katsuwonus pelamis) contains a high level of docosahexaenoic acid combined with phospholipids. In this study, we examined the effect of OLS in male Wistar rats given OLS mixed in feed (0.9%) for 42 days, using an animal model of anxiety, the elevated T-maze test. The avoidance latency at the 1st trial was significantly shorter in the OLS ingestion group than in the control group. Those at the 2nd and 3rd trials showed a similar tendency. There was almost no differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The same is true of the serum components TG and NEFA. In addition, the HDL concentration was lower in the OLS groups, as reported previously [14,15]. Although no signif-icant difference test was performed because an interaction of the stress and OLS factors was observed, the OLS group under chronic stress, compared with the control group, tended to have a lower CORT level.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The same is true of the serum components TG and NEFA. In addition, the HDL concentration was lower in the OLS groups, as reported previously [14,15]. Although no signif-icant difference test was performed because an interaction of the stress and OLS factors was observed, the OLS group under chronic stress, compared with the control group, tended to have a lower CORT level.…”
Section: Discussionsupporting
confidence: 76%
“…In previous experiments with rats, we found that OLS inhibited the increase in corticosterone (CORT) production under acute stress, stimulated the secretion of dehydroepiandrosterone (often referred to as the antistress hormone) [1,6], and accelerated the decrease in CORT levels following relief from stress [14]. In addition, elevated T-maze tests [5,7,16,21] demonstrated that OLS had the ability to mitigate anxiety and/or fear [15].…”
mentioning
confidence: 99%
“…Previously, we studied anxiety and/or fear using an elevated T-maze test with rats given OLS. We found that OLS shortened avoidance latency at the first trial, indicating that it has an effect against anxiety and/or fear [9]. In the present study, we evaluated the anti-anxiety effect of OLS using an elevated plus-maze test [1, 3, 4, 6-8, 12, 15], which is often used to determine anxiety level.…”
mentioning
confidence: 99%
“…As OLS is rich in n-3 fatty acids, the control feed was prepared to give the same energy percentage as n-3 fatty acids and the same n-6/n-3 ratio [9]. In the present study, rats were also given OLS mixed as a lipid component in feed.…”
mentioning
confidence: 99%